ANALISIS SISTEM PENGELOLAAN BARANG MILIK DAERAH PADA BADAN PENDAPATAN DAN ASET DAERAH PROVINSI NUSA TENGGARA TIMUR - Brandon Rafaello Elim; Thobias E.D. Tomasowa; Puteri Ayu Pratiwi (P3M- Politeknik Negeri Kupang, 2021)
This research was conducted because there were still many problems, such as errors in recording items due to the expansion of the location and the unavailability of adequate storage space. It makes moveable items such as laptops and LCD projectors uncontrollable, etc. and fragile. This research was conducted to determine the Regional-Owned Assets Management System at the Badan Pendapatan dan Aset Daerah of East Nusa Tenggara Province.The research design used in this research is quantitative data, qualitative data, while the data sources used are primary data and secondary data. The research method used in this research is descriptive qualitative.The research results show that the management of regional-owned asset at the Badan Pendapatan dan Aset Daerah has been doing well and under the systems and procedures of the regional-owned asset management cycle as regulated in PERMENDAGRI NO. 19 of 2016 concerning guidelines for the management of the regional property. But not all have been maximally implemented, such as several obstacles or inhibiting factors encountered in the implementation of regional-owned asset management, namely the human resource (HR) factor because of the need for knowledge and understanding of HR in managing a regional-owned asset